Household Characteristics and Poverty Line Assessment in Rural Communities - Muhammad Ichsan; Armin Muis; Muhtar Lutfi; Nudiatulhuda Mangun; Andi Herman Jaya (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the characteristics of poor households and measure the poverty line, poverty level, depth of poverty, and severity of poverty in Lumbudolo Village, Central Banawa District, Donggala Regency. The study also examines the influence of socio-economic factors and livelihood assets on poverty status based on the Sustainable Livelihood Framework (SLF). A mixed-methods approach was applied through a survey of 51 household heads, in-depth interviews, and focus group discussions. Data were analyzed using descriptive statistics, poverty indicators (P0, P1, P2), the Gini Ratio, and logistic regression. The results show that most poor households are headed by elderly individuals with low levels of education and are primarily employed in the agricultural and informal labor sectors. Average household income ranges from IDR 250,000 to IDR 500,000 per month, with expenditures dominated by food consumption. Lumbudolo Village exhibits moderate income inequality (Gini Ratio = 0.549), and nearly half of its households fall below the poverty line. The P1 and P2 values indicate substantial depth and severity of poverty. Logistic regression analysis reveals that human, financial, and physical capital significantly influence the likelihood of households experiencing poverty, whereas basic socio-economic characteristics show limited effects. These findings emphasize that poverty is multidimensional, requiring development interventions that prioritize improvements in human resource quality, access to financial capital, and basic infrastructure to strengthen household resilience and reduce poverty sustainably.